Cardiac arrest associated with reperfusion of the liver during transplantation: incidence and proposal for a management algorithm. (27th December 2012) - Aufhauser, David D.; Rose, Tom; Levine, Matthew; Barnett, Rebecca; Ochroch, E. Andrew; Aukburg, Stanley; Greenblatt, Eric; Olthoff, Kim; Shaked, Abraham; Abt, Peter
Abstract Cardiac arrest associated with reperfusion of the liver allograft in a euvolemic patient is a rare but potentially devastating event. There are few case series describing experience with this complication and no published management protocols guiding treatment. This article is a retrospective case series of patients experiencing post‐reperfusion intraoperative cardiac arrest between 1997 and 2011. Among 1581 liver transplants, 16 (1%) patients experienced post‐reperfusion cardiac arrest. Among patients with intraoperative arrests, 14 (88%) patients required open cardiac massage. Seven (44%) were placed on cardiopulmonary bypass (CPB) when cardiac activity failed to adequately recover. Placement on CPB reversed cardiac pump failure and established a perfusing rhythm in six of seven (86%) recipients, leading to one of seven (14%) intraoperative mortality. Recovery of myocardial function was associated with low early survival with only 3/7 (43%) patients who underwent CPB surviving until discharge. Among all patients who survived the perioperative period, one‐yr survival was 70% (N = 7), and five‐yr survival was 50% (N = 5). Cardiac arrest during liver transplantation is associated with a poor prognosis during the perioperative period. In patients who do not recover cardiac activity after standard resuscitative measures, progression to physiologic support with systemic anticoagulation and CPB may allow correction of electrolyte derangements, maintenance of cerebral perfusion, and myocardial recovery.